The Routledge handbook of Hindu temples
1 online resource (xix, 496 pages)
Keywords: "This handbook is a comprehensive study of the archaeology, social history, and the cultural landscape of the Hindu temple. Perhaps the most recognizable of the material forms of Hinduism, temples are lived, dynamic spaces that are significant sites of the creation of cultural heritage, both in the past and the present. Drawing on historiographical surveys and in-depth case studies, the volume centres the material form of the Hindu temple as an entry point to study its many adaptations and transformations from the early centuries CE to the 20th century. It highlights the vibrancy and dynamism of the shrine in different locales and studies the active participation of the community for its establishment, maintenance, and survival. The illustrated handbook takes a unique approach by focusing on the social base of the temple rather than its aesthetics or chronological linear development. It fills a significant gap in the study of Hinduism and will be an indispensable resource for scholars of archaeology, Hinduism, Indian history, religious studies, museum studies, South Asian history, and Southeast Asian history"--